MUTUAL LEGAL ASSISTANCE TREATIES (MLATs) SEBAGAI INSTRUMEN PEMBERANTASAN KEJAHATAN INTERNASIONAL - Noer Indriati (Jurnal Dinamika Hukum, 2009)
International contractual law is an order which must respect and adhered by pertinent of the parties in agreement. The formal and informal relation between the citizen or corporate have very intensively. International badness which pass boundaries jurisdiction of the state have increase in the form which is sophisticated and the frequency which progressively often. Because of international badness which have more progressively is needed cooperation between the state which it is more coordinated as straightening of law. Mutual Legal Assistance Treaties (MLATS) emerge because eradication of insufficient badness upheld by agreement of extradition. Form of Mutual Legal Assistance Treaties (MLATS) have agreed on, for example United Nations Convention Against Corruption Year 2003, United nations Conventions Against Transnational Organized Crime Year 2000. While in the level of ASEAN, Treaty Mutual Legal Assistance in Criminal Matters year 2004. Kata kunci: kejahatan internasional, perjanjian internasional